Reading (in) the Holocaust Practices of Postmemory in Recent Polish Literature for Children and Young Adults. - Wójcik-Dudek, Małgorzata (Studies in Jewish History and Memory, 2020)
The book deals with the issue of the Holocaust in the Polish literature for children and adolescents. Drawing upon some of the leading Polish authors of the twentieth and the twentieth-first centuries, the author reveals the historical, ideological, and cultural entanglement of their works. The main focus of the book is to search for reasons behind the outpouring of interest in the Holocaust noticed in the most recent Polish literature for younger readers. Among these reasons, the author lists the Polish local and historical context, the new approach to issues traditionally seen as taboo, the development of memory and postmemory narratives, and the postmodern shift from a discursive totality and universalist explanations.